A Comprehensive Study of Di Diesel Engine Performance Withvegetable Oil: An Alternative Bio-Fuel Source of Energy - A. K., Azad (Universiti Malaysia Pahang, 2012)

(untitled)
This study offers comprehensive details on the use of bio-fuel as a viable and alternative source of energy. The bio-fuel was prepared from vegetable oil, i.e., mustard oil and tested in a diesel engine in both pure form and as a diesel blend. The mustard oil blend proportions were 20%, 30%, 40% and 50% and named as bio-diesel blends B20, B30, B40 and B50. A fuel-testing laboratory determined the properties of the pure mustard oil fuel and its blends, i.e., density, viscosity, dynamic viscosity, carbon residue, flash point, fire point and calorific value. An assessment of engine performance, i.e., brake horsepower (bhp), brake specific fuel consumption (bsfc), brake thermal efficiency (bte) and brake mean effective pressure (bmep) etc., was carried out for pure diesel, pure mustard and the blends, both in laboratory conditions and under British Standard (BS) conditions. Finally, an analysis and comparison was made of the effects of the various fuels on the different engine properties.